Look at the Polyphony and Theoretical Heritage of S.I.Taneev - Azimjon Khojimamatov; Farangiz Ikromova (Genius Journals, 2022)
This article discusses the polyphony of the work of Sergei Ivanovich Taneev, a famous composer, who contributed to the world music culture with his unique musical works, and his theoretical heritage
Keywords: Polyphony; music; index; music form